Motels, hotels, restaurants, and bars. (New York : McGraw Hill Education, 1960)
This book is primarily concerned with good planning and design. Almost all of the articles in it originally appeared in Architectural Record, and were chosen by its editors to illustrate these principles.
Section 1: Motels -- Section 2: Hotels -- Section 3: Restaurants and bars.
Includes bibliographical references.
Keywords: TOURIST CAMPS, HOSTELS, ETC